PENGARUH NILAI PERUSAHAAN, LEVERAGE DAN FINANCIAL DISTRESS TERHADAP KEPUTUSAN HEDGING STUDI KASUS PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Ahmad Pati Hulmubin; Furqonti Ranidiah; Yudi Partama Putra; Diah Khairiyah (Universitas Muhammadiyah Bengkulu, 2025)
financial distress on hedging decisions in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. The method used is a quantitative approach with logistic regression analysis techniques. The sample consisted of 45 companies selected using a purposive sampling method. The independent variables studied include firm value (Market to Book Value), leverage (Debt to Equity Ratio), and financial distress (Altman Z-Score), while the dependent variable is the hedging decision measured using a dummy. The results show that firm value has a positive and significant effect on hedging decisions, while leverage and financial distress have a negative and significant effect. Simultaneously, these three variables have a significant influence on hedging decisions. However, the ability of these three variables to explain hedging decisions is only 7.8%, the rest is influenced by other factors outside the research model. Keywords: Firm Value, Leverage, Financial Distress, Hedging Decisions, Logistic Regression